2021
DOI: 10.1002/tqem.21767
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of groundwater quality in Jampali coal mine, Raigarh, Chhattisgarh, India

Abstract: Groundwater is the main source of water for drinking, industrial, and irrigation uses for most nations. Groundwater quality deterioration occurs due to urban, agricultural, mining, and industrial expansions. This research deals with the assessment of groundwater quality index, correlation, clustering analysis, and major ions chemistry around Jampali opencast coal mine of Raigarh district, Chhattisgarh, India, where groundwater is the main source of drinking water. A total of 28 groundwater samples were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Former studies demonstrated that groundwater contribution is important for sustaining stream flow during dry spells and that the geology (bedrock and alluvial lithologies, tectonic setting) of a catchment is a crucial factor in controlling this contribution (Arnott et al., 2009; Wirth et al., 2020). Coal mining influence the subsurface water in terms of its level, quantity, and quality (Ahmed, Sonkar et al., 2022; Ahmed, Sonkar, Kishore et al., 2022; Chandra et al., 2015; Mahato et al., 2016; Rakotondrabe et al., 2018; Tiwari et al., 2016; Vishwakarma, Behera et al., 2020). The groundwater levels in and around mining areas vary to a great extent from place to place.…”
Section: Introductionmentioning
confidence: 99%
“…Former studies demonstrated that groundwater contribution is important for sustaining stream flow during dry spells and that the geology (bedrock and alluvial lithologies, tectonic setting) of a catchment is a crucial factor in controlling this contribution (Arnott et al., 2009; Wirth et al., 2020). Coal mining influence the subsurface water in terms of its level, quantity, and quality (Ahmed, Sonkar et al., 2022; Ahmed, Sonkar, Kishore et al., 2022; Chandra et al., 2015; Mahato et al., 2016; Rakotondrabe et al., 2018; Tiwari et al., 2016; Vishwakarma, Behera et al., 2020). The groundwater levels in and around mining areas vary to a great extent from place to place.…”
Section: Introductionmentioning
confidence: 99%